Efeito de uma cartilha educativa sobre o sono de crianças egressas da unidade neonatal: avaliação do conhecimento, atitude e prática dos pais - Oliveira, Lusiana Moreira de (2020)
Sleep is identified as the main brain function in early childhood, being important for child growth and development. The objective of this study was to evaluate the effect of the educational booklet “Taking care of the child's sleep” on the knowledge, attitude and practice of parents of children discharged from the neonatal unit. Quasi-experimental study, the intervention type before and after, carried out in a specialized pediatric outpatient clinic at the Federal University of Ceará - UFC, with 50 parents of children aged 0 to 24 months. Inclusion criteria: father / mother from the neonatal unit; be present on the day of the consultation; be considered the main caregiver; sleeping with the child at night; have a fixed or mobile phone; be literate; reside in the great Fortaleza (great fortress). Parents of children with biological or pathological changes were excluded; parents who have a hearing impairment. Data collection was carried out from November / 2019 to March / 2020. A form was used for sociodemographic characterization of parents and perinatal of children, the KAP survey (Knowledge, Attitude and Practice) and the educational booklet as an intervention. In the pretest, the parents read the booklet and, after 15 days, the post-test was carried out by telephone. The Wilcoxon test and Student's t test were used to compare proportions and means in the pre and post-test, respectively. Approved by the UFC Research Ethics Committee, opinion number 17946619.7.0000.5054. The sample of parents was predominantly female (94%), 25 to 34 years old (44%), in a consensual union (46%), with complete or incomplete high school (76%), income equal to one minimum wage (38%). In relation to children, most were born preterm (82%), aged from zero to six months (62%), from 2000 to 2499 grams (60%), admitted to the Neonatal Intensive Care Unit (68%), from 1 to 10 days (50%), due to prematurity (48%). As for infant sleep, sleeping in a crib in the parents' room and between 6 pm and 9 pm were the most prevalent variables. After reading the booklet and applying the post-test, there was an increase in the means of knowledge, attitude and practice related to sociodemographic variables, mainly living with the spouse, having completed or incomplete high school and earning a minimum wage. Prematurity and the child's age up to six months showed higher averages in the post-test, as well as hospitalization Conventional neonatal intermediate care unit, due to prematurity or low birth weight in knowledge and attitude. Sleeping in the parents' bed showed a greater increase in means in the KAP and p values ≤0.05. In view of the above, it is noteworthy that after using the educational booklet, the parents' average scores on knowledge, attitude and practice have increased considerably, 12 reinforcing the importance of advising parents on infant sleep, using valid educational materials, that can assist them in obtaining knowledge, in developing attitude and practice for quality and safe sleep. The use of the KAP methodology allowed to know the studied population, in which it was identified what the parents know, think and how they act in the promotion of infant sleep. In addition, it was possible to identify the real gaps in the knowledge, attitude and practice that may predispose or hinder the sleep quality of these children.